Lessons learned in using realist evaluation to assess maternal and newborn health programming in rural Bangladesh - Adams, Alayne; Sedalia, Saroj; McNab, Shanon; Sarker, Malabika (© 2016 Oxford University Press, 2016)
This article was published in Health Policy and Planning [© 2016 Oxford University Press] and the definite version is available at: http://heapol.oxfordjournals.org/content/early/2015/06/22/heapol.czv053.short?rss=1